THE CONCEPT OF DISTRIBUTIONAL JUSTICE IN TAX POLICY: A COMPARATIVE STUDY BETWEEN THE THEORIES OF JOHN RAWLS AND ROBERT NOZICK - Putu Arya Aditya Pramana; Kadek Januarsa Adi Sudharma; I Gede Agus Kurniawan; Rahel Asefa (Kanun Jurnal Ilmu Hukum, 2025)
The ideal tax policy should balance social justice through income redistribution, as proposed by John Rawls, with economic freedom and individual property rights, as emphasized by Robert Nozick, to create a fair and sustainable system. This study aims to analyze the differences and similarities in the theories of distributive justice according to John Rawls and Robert Nozick in normative, philosophical, and sociological aspects, as well as examine their implications for tax policy to formulate an ideal taxation system based on both theories. This research employs a normative legal method with conceptual, legislative, and comparative approaches to analyze the theories of distributive justice by Rawls and Nozick in tax policy, using a literature study technique and descriptive-comparative analysis of tax regulations in various countries. The findings reveal that differences in the theories of distributive justice between Rawls and Nozick have significant implications for tax policy, where Rawls advocates progressive taxation to reduce social inequality and improve the welfare of disadvantaged groups, whereas Nozick rejects tax redistribution as it violates individual property rights and supports a proportional tax system instead. Philosophically, Rawls is based on social contract theory and the veil of ignorance to create policies that are fair for all, while Nozick emphasizes entitlement theory, which opposes state intervention in wealth distribution. In practice, countries with strong welfare systems, such as Sweden and Canada, align more with Rawls' theory, whereas countries emphasizing economic freedom, such as the United States and Singapore, are more in line with Nozick. Therefore, an ideal tax policy could adopt a mixed approach, with moderate progressive taxation to support social welfare and lower corporate taxes to encourage investment and economic growth, thereby balancing social justice and individual freedom